Waste Bank Management Information System - Kraugusteeliana, Kraugusteeliana; Anita Muliawati; Sri Mulyantini; Satria Yudha Widjaya; Anwar Nassihin; Nayla Tinneke Kusmawardhani; Della Chintiya Dewi; Ananda Alvi Al Fadhli (Yayasan Gema Bina Nusantara, 2024)
Waste bank management is becoming increasingly popular to create a clean and comfortable environment. For this reason, it is important to have an Android-based waste bank application as an alternative solution to the waste problem in society. The waste management application also provides education regarding public concern for cleanliness and concern for the environment so that it can create an environment that is clean and free from waste. Management of this waste bank will improve the economy for the community because there is rupiah value obtained from the sale of waste banks in the community. This waste bank application also consists of waste pickup, transaction, and education features. The method used for waste management is to carry out transactions directly, and its use can be displayed using an Android smartphone, since almost all people have a cellphone to carry out waste bank management transactions. This information system application provides economic value to the community because the results from the disposal of sorted waste can be sold into funds or money as savings that can be withdrawn at the end of each month.